Evolution of visual guanylyl cyclases and their activating proteins with respect to clade and species-specific visual system adaptation - Gesemann, Matthias; Neuhauss, Stephan C. F. (Frontiers in Molecular Neuroscience, 2023)
Membrane guanylyl cyclase receptors are important regulators of local cGMP production, critically influencing cell growth and differentiation as well as ion transport, blood pressure and calcium feedback of vertebrate phototransduction. Currently, seven different subtypes of membrane guanylyl cyclase receptors have been characterized. These receptors have tissue specific expression and are activated either by small extracellular ligands, changing CO2 concentrations or, in the case of visual guanylyl cyclases, intracellularly interacting Ca2+-dependent activating proteins. In this report, we focus on the visual guanylyl cyclase receptors (GCs) GC-E (gucy2d/e) and GC-F (gucy2f) and their activating proteins (GCAP1/2/3; guca1a/b/c). While gucy2d/e has been detected in all analyzed vertebrates, GC-F receptors are missing in several clades (reptiles, birds and marsupials) and/or individual species. Interestingly, the absence of GC-F in highly visual sauropsida species with up to 4 different cone-opsins is compensated by an increased number of guanylyl cyclase activating proteins, whereas in nocturnal or visually impaired species with reduced spectral sensitivity it is consolidated by the parallel inactivation of these activators. In mammals, the presence of GC-E and GC-F is accompanied by the expression of one to three GCAPs, whereas in lizards and birds, up to five different GCAPs are regulating the activity of the single GC-E visual membrane receptor. In several nearly blind species, a single GC-E enzyme is often accompanied by a single variant of GCAP, suggesting that one cyclase and one activating protein are both sufficient and required for conferring the basic detection of light.